15.8% efficiency binary all-small-molecule organic solar cells enabled by a selenophene substituted sematic liquid crystalline donor. Issue 10 (17th August 2021) - Xu, Tongle; Lv, Jie; Yang, Ke; He, Ya; Yang, Qianguang; Chen, Haiyan; Chen, Qianqian; Liao, Zhihui; Kan, Zhipeng; Duan, Tainan; Sun, Kuan; Ouyang, Jianyong; et al.
Abstract : A selenophene substituted sematic liquid crystalline donor is developed to achieve outstanding PCEs for binary ASM-OSCs (15.8%) and thick-film ASM-OSCs (14.3%). Abstract : Selenophene substitution of photovoltaics materials can improve their intermolecular interactions and thus offer a good opportunity to finely optimize their phase separation morphology to an ideal state. However, the performance of this substitution strategy is yet unclear in liquid crystalline donors, which have demonstrated high efficiency. The combination of those structural advantages may help to achieve state-of-the-art device performance. Herein, two new liquid crystalline small molecule donors are designed and synthesized with different substituents on benzo[1, 2- b :4, 5- b ′]dithiophene (BDT) central units, including L1 with thiophene group and L2 with selenophene group, for investigating the effect of selenophene substitution on morphology and photovoltaic performance of liquid crystalline donors. Unlike the control donor L1, the selenide donor L2 shows a higher intramolecular interaction and presents a novel sematic liquid crystal phase, which results in a more favored morphology, better light harvest, and lower charge recombination. As a result, outstanding power conversion efficiency up to 15.8% is realized in the L2 :Y6 based devices. Particularly promising is the fact that selenide-based devices with active layer thicknesses up to ∼300 nm can still output a high PCE of 14.3%, which is promising for roll-to-roll printing processes with large-scale production. To our best knowledge, the PCEs of 15.8% and 14.3% are the highest values reported to date in binary ASM-OSCs and thick-film ASM-OSCs, respectively. These excellent values demonstrated the superiority of selenophene in the construction of efficient small molecule liquid crystalline donors.